Tinjauan Hukum Islam terhadap Putusan PN Sidoarjo No. 189/Pid.B/2009/PN.Sda Tentang Pemerkosaan Anak di Bawah Umur - Asyifa, Asyifa (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
The purpose of this paper is to find out a review of Islamic criminal law on the Sidoarjo District Court's decision on the crime of rape against minors. The research results obtained explain that the legal basis used by the judge in deciding case No. 189 / Pid.B / 2009 / PN.Sda, using article 81 paragraph 1 of the Child Protection Law No. 23 of 2002. Whereas in practice the Sidoarjo District Court only imposes a 7-year prison sentence and a fine of Rp. 60,000,000, -, a 5-month subsidy based on considerations of burdensome and mitigating matters. In Islamic criminal law, punishment for the perpetrator of the criminal act of rape is equated with adultery. From an Islamic point of view, the sentencing of the Sidoarjo District Court to the perpetrator of rape against minors is deemed unbalanced, when viewed from the perspective of the consequences of the act committed by the perpetrator against the victim, and it does not preclude the perpetrator from repeating the same act, because considered mild enough and could not cause a deterrent effect.